Karakteristik Organoleptik dan Kimia Formulasi Pasta Ubi Jalar Kuning dan Tepung Terigu Dalam Pembuatan Brownies - Gay, Muhammad L; Augustyn, Gelora H; Mailoa, Meitycorfrida (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to determine the organoleptic and chemical properties of yellow sweet potato brownies made from yellow sweet potato paste and wheat flour. This research was conducted at the Agricultural Product Technology Laboratory, Faculty of Agriculture, Pattimura University, and analyzed at the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Pattimura University, starting from March 2021 to completion. This research is an experimental study in a laboratory using 4 levels of treatment for the formulation of yellow sweet potato paste and wheat flour 50:200, 100:150, 150:100, and 200:50, and it’s repeated three times. The results of the research from organoleptic results selected the P1 treatment (50 g yellow sweet potato paste and 200 g wheat flour) as a treatment for chemical tests. Chemical test results obtained a water content of 16.58%. 0.56% ash content, 7.08% protein, 25.24% fat and 50.54% carbohydrates.